Korelasi Antara Kualitas Sistem Informasi Terhadap Efisiensi Pemanfaatan Sistem Informasi Media Informasi Lowongan Kerja Pada PT. Sentra Karya Sentosa Purwokerto - Adhi Wibowo; GH Sumartono; Andreas Devano (Jurnal HUMMANSI (Humaniora, Manajemen, Akuntansi), 2020)
In this day and age, technology is needed by companies around the world, including in Indonesia. One of the technologies needed and has been widely used is the Internet. Internet has an important role for companies to support their work. Work can be completed faster without being hindered by space and time. At PT. Sentra Karya Sentosa Purwokerto, the work application process used is still manual and the promotional media used is still simple. Therefore the authors conclude the problems in the field of job application and the media for job promotion. With this, it is hoped that it can help make it easier for job applicants to find job vacancy information and make it easier for job providers to promote job vacancies. Information Systems Media Information Job Vacancies For Job Applicants At PT. Sentra Karya Sentosa Purwokerto based on the website has been tested with a correlation test. The correlation value of the quality of information systems on efficiency is Sig. 0.002 <0.05 indicates that there is a significant relationship. From the results of these tests, it is concluded that the Information Media Information System for Job Vacancies for Job Applicants at PT. Sentra Karya Sentosa Purwokerto has a significant effect on the efficiency of job applications.